Advanced Process Control Applications to Water Resources Systems: Two Industrial Case Studies. Issue 33 (2022) - Zanoli, S.M.; Pepe, C.; Astolfi, G.
Abstract: This paper presents two industrial case studies where Advanced Process Control techniques have been applied. The first case study is represented by a hydroelectric plant located in Italy. In this plant, a model predictive controller has been designed and installed, in order to optimally satisfy the production plan. The predictive control approach has been motivated by the availability of forecasts on water requests by the hydroelectric plant and by the goodness of fit performances of the obtained linear process model. The second case study is represented by a pumping station located in an Italian Water Distribution Network. Advanced control logics have been designed in order to optimally and automatically manage the scheduling of the involved pumps. The developed Advanced Process Control systems have been successfully installed on the real plants, obtaining energy efficiency and process control improvement.